Importmodellen i norsk fengselsvesen - Inger Marie Fridhov; Torfinn Langelid (Nordisk Tidsskrift for Kriminalvidenskab)
Until 1969, the Norwegian Prison Service was itself responsible for providing health, educational and other services offered to inmates. This was referred to as the “self-sufficiency model”. In 1969, however, the Ministry of Education and Research assumed financial and professional responsibility for the education of prisoners. This was the start of a process in which the responsibility for many services was transferred from the Ministry of Justice to the agencies that typically provide these services to the general public. This reorganization was based on the ideology that a prison sentence should involve, as far as practically possible, no more than the deprivation of liberty. Ergo, other civil rights and entitlements should not be lost or restricted. Professor Nils Christie was a primus motor for this reorganization of prison operations, and it was he who coined the phrase “the import model”. The following article describes the implementation of the import model from 1969 to the present and some of its consequences.